ANALISIS PENERAPAN ETIKA BISNIS ISLAM PADA NURUL HAYAT RETAIL SURABAYA PERSPEKTIF IMAM AL-GHAZALI - Muhammad Pria Imam Hidayat; Mustofa Mustofa (CV. Denasya Smart Publisher, 2026)
This study examines the implementation of Islamic business ethics at Nurul Hayat Retail Surabaya and identifies the supporting and inhibiting factors affecting its consistency in daily operations. As a retail unit operating under a philanthropic institution, Nurul Hayat Retail integrates profit-oriented activities with moral, social, and spiritual responsibilities. This research adopts a qualitative approach using a case study method. Data were collected through observation, semi-structured interviews with management and employees, and documentation. The analysis is grounded in the principles of Islamic business ethics tauhid, justice (al-‘adl), responsibility (mas’uliyah), and benevolence (ihsan) viewed through Imam Al-Ghazali’s moral framework, which distinguishes between obligatory morality (al-‘adl) and recommended morality (ihsan).The findings reveal that Nurul Hayat Retail has generally implemented Islamic business ethics at the level of obligatory morality, particularly in pricing transparency, honesty in transactions, fulfillment of employee rights, and avoidance of fraudulent practices. Elements of ihsan are reflected in ethical customer service and the integration of social values into business activities; however, their application remains inconsistent. Key inhibiting factors include limited human resources, overlapping job responsibilities, and the absence of a well-structured management system, while strong institutional values, a religious organizational culture, and commitment to social missions serve as supporting factors. This study contributes to the literature by highlighting the ethical dynamics of Islamic retail practices within a philanthropic institutional context and emphasizing the need for strengthened managerial systems to enhance the consistent application of ihsan.